Factors Predictive of Voice and Swallowing Outcomes after Anterior Approaches to the Cervical Spine. (23rd December 2013) - Mehra, Saral; Heineman, Thomas E.; Cammisa, Frank P.; Girardi, Federico P.; Sama, Andrew A.; Kutler, David I.
Abstract : Objective: To quantify the incidence of postoperative voice, swallowing, and other problems, including time to resolution following anterior transcervical approaches to the cervical spine, and to assess surgical factors associated with outcomes. Study Design: Historical cohort study. Setting: Academic medical center. Subjects and Methods: One hundred eighty‐eight consecutive patients with cervical spine disease who underwent an anterior transcervical approach to the spine by a single head and neck surgeon over a 4‐year time period. Rather than primary, single‐level approaches, all patients in this study had multilevel, high‐cervical (above C4), low‐cervical (below C6), and/or revision approaches. Postoperative voice, swallowing, and other complaints were measured as well as time to resolution using Kaplan‐Meier method. Surgical factors related to outcomes were analyzed using regression analysis. Results: Follow‐up was available for 129 patients, with average and median time of 35 months. Seventy‐seven patients (60%) had a postoperative issue, including 35 patients (27%) with postoperative voice complaint, 62 patients (48%) with postoperative swallowing complaint, and 16 patients (12%) with other problems. Swallowing and voice complaints persisted beyond 1 year in 28% and 9% of patients, respectively. Approaching spinal levels above C4 and exposing more than 3 spinal levels were 2 factors significantly related to voice and swallowing problems. Conclusion: There is a high incidence of subjective voice and swallowing complaints following transcervical anterior approaches to the spine, and such complaints can persist beyond 1 year in many patients. Exposure of more than 3 spinal levels or above level C4 are 2 factors significantly associated with outcome.